Optimalisasi Kinerja di Dinas Perkebunan Kaltim: Peran Pelatihan, Komitmen, dan Motivasi - Nendra, Andre Ray; Sabtohadi, Joko; Rahmah, Asmadhini Handayani; Rahmadi, Muhammad Harry (Equator Journal of Management and Entrepreneurship (EJME), 2024)
In the last 3 years, the need for competence in participating in training is very lacking, so that employee commitment and employee motivation are less than satisfactory due to the incomplete database on the conditions and development potential of the East Kalimantan Provincial Plantation Service. This study aims to determine the effect of training variables, commitment, and motivation on employee performance. The research method used is field research using a quantitative approach where the population is the same as the sample and totals 47 civil servants and non-civil servants and the data is processed using SPSS version 26. The results of the analysis show that the training variable has no significant effect on the employee performance variable, the commitment variable has no significant effect on the employee performance variable, the motivation variable has a significant effect on employee performance, the training, commitment and motivation variables simultaneously have a significant effect on employee performance, the motivation variable has more effect on employee performance, and the effect of training, commitment and motivation variables on the performance of employees of the Plantation Service of East Kalimantan Province is 0.635 or 63.5%, the remaining 36.5% is influenced by other variables not examined in this study.